Exercise derived myokine irisin as mediator of cardiorespiratory, metabolic and thermal adjustments during central and peripheral chemoreflex activation - Bernardes-Ribeiro, Mariana [UNESP]; Patrone, Luis Gustavo A. [UNESP]; Cristina-Silva, Caroline [UNESP]; Bícego, Kênia C. [UNESP]; Gargaglioni, Luciane H. [UNESP] (Springer Nature, 2024)
Exercise elicits physiological adaptations, including hyperpnea. However, the mechanisms underlying exercise-induced hyperpnea remain unresolved. Skeletal muscle acts as a secretory organ, releasing irisin (IR) during exercise. Irisin can cross the blood–brain barrier, influencing muscle and tissue metabolism, as well as signaling in the central nervous system (CNS). We evaluated the effect of intracerebroventricular or intraperitoneal injection of IR in adult male rats on the cardiorespiratory and metabolic function during sleep–wake cycle under room air, hypercapnia and hypoxia. Central IR injection caused an inhibition on ventilation (VE) during wakefulness under normoxia, while peripheral IR reduced VE during sleep. Additionally, central IR exacerbates hypercapnic hyperventilation by increasing VE and reducing oxygen consumption. As to cardiovascular regulation, central IR caused an increase in heart rate (HR) across all conditions, while no change was observed following peripheral administration. Finally, central IR attenuated the hypoxia-induced regulated hypothermia and increase sleep episodes, while peripheral IR augmented CO2-induced hypothermia, during wakefulness. Overall, our results suggest that IR act mostly on CNS exerting an inhibitory effect on breathing under resting conditions, while stimulating the hypercapnic ventilatory response and increasing HR. Therefore, IR seems not to be responsible for the exercise-induced hyperpnea, but contributes to the increase in HR.
Keywords: Heart rate; Myokine; Sleep; Ventilation